2015
DOI: 10.4067/s0034-98872015000700002
|View full text |Cite
|
Sign up to set email alerts
|

Desarrollo de neoplasia en pacientes con enfermedad inflamatoria intestinal

Abstract: Background: The chronic inflammation of the intestinal mucosa, the extra-intestinal manifestations of the disease and the immunosuppressive treat (Rev Med Chile 2015; 143: 834-840)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 37 publications
0
1
0
1
Order By: Relevance
“…But the occurrence of vascular malformation has not been linked to this treatment. 7 Thus, it can be concluded that neither DC nor its treatment appears to be related to the onset of bowel vascular malformation; however, considering the lack of articles addressing this issue, our report plays a big role, thanks to the documentation of the observed complication, as an eventual contribution to other publications that may arise.…”
Section: Discussionmentioning
confidence: 84%
“…But the occurrence of vascular malformation has not been linked to this treatment. 7 Thus, it can be concluded that neither DC nor its treatment appears to be related to the onset of bowel vascular malformation; however, considering the lack of articles addressing this issue, our report plays a big role, thanks to the documentation of the observed complication, as an eventual contribution to other publications that may arise.…”
Section: Discussionmentioning
confidence: 84%
“…Actualmente el estudio de enfermedad celíaca se ha orientado a sus consecuencias más frecuentes que son la obstrucción intestinal cuyo tratamiento es quirúrgico (6) y los tumores de intestino delgado con menor frecuencia, pero de importancia mayor debido a que los linfomas se manifiestan con malabsorción severa que no responde a una dieta libre de gluten y está asociada a una alta tasa de mortalidad (7,8). El tratamiento de estos pacientes debe estar guiado según su severidad, sin limitar las opciones terapéuticas, para prevenir el desarrollo de neoplasia, manteniendo el seguimiento clínico de los pacientes para vigilar su evolución y controlar el crecimiento en los niños, así como el cumplimiento de la dieta y prevenir déficits nutricionales (9,10). Debido a que la enfermedad celíaca tiene un impacto sustancial en las funciones psicológicas, las relaciones familiares y sociales con los pacientes diagnosticados, estos requieren una asistencia clínica biopsicológica para una mejor adherencia al tratamiento y la calidad de vida de los pacientes (11).…”
Section: Introductionunclassified